1992
DOI: 10.1080/00380768.1992.10416496
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen management and fertilizer use efficiency for lowland rice in Pakistan

Abstract: With a view to develop simpler techniques for improving the efficiency of nitrogen fertilizer use for lowland rice, field studies were conducted in 1986 and 1987. During 1986, dry soil incorporation of urea was compared with puddled soil application of urea and calcium ammonium nitrate (CAN) and deep placement of urea super granule (USG). In 1987, the application of urea in puddled soil without standing water (soil saturation) was compared with the application in standing water and deep placement of USG. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The clayey, alkaline and calcareous nature of soils in Pakistan, Zn fertilizer is mainly fixed by soil particles and very low amount is available and uptake by rice crop plants (Tahir et al 1991 ) and so the residual Zn in soils could increase productivity of subsequent wheat crop under rice–wheat cropping system. Zia et al ( 1996 ) reported that residual effect of the higher rate of 10 kg Zn ha −1 was most beneficial to increase rice GY than the low rate of 5 kg Zn ha −1 under RWCS. Likewise, Hussain ( 2004 ) reported that the residual Zn (5 kg ha −1 ) increased the paddy GY by 6.1 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clayey, alkaline and calcareous nature of soils in Pakistan, Zn fertilizer is mainly fixed by soil particles and very low amount is available and uptake by rice crop plants (Tahir et al 1991 ) and so the residual Zn in soils could increase productivity of subsequent wheat crop under rice–wheat cropping system. Zia et al ( 1996 ) reported that residual effect of the higher rate of 10 kg Zn ha −1 was most beneficial to increase rice GY than the low rate of 5 kg Zn ha −1 under RWCS. Likewise, Hussain ( 2004 ) reported that the residual Zn (5 kg ha −1 ) increased the paddy GY by 6.1 %.…”
Section: Discussionmentioning
confidence: 99%
“…The major cause of low yield under RWCS is nutrients depletion from the soil (Dawe 2000 ; Shah et al 2011 ). The continuous RWCS for several decades has thus resulted in nutrients depletion and decline in yields (Zia et al 1996 ; Hobbs and Morris 1996 ; Dawe 2000 ; Duxbury 2000 ; Shah et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since, it is clear from the data, that minimum N losses were detected from mixture fertilization even at lower rate, which conclusively resulted in enhancing apparent nitrogen recovery. Zia et al (1992) have reported similar elucidations. On the basis of this study, it could thus be inferred that apparent nitrogen recovery and physiological efficiency of rice crop can be improved through the blended application of urea and ammonium sulphate (1:1) in the salt-affected soil.…”
Section: Resultsmentioning
confidence: 59%
“…There were number of reasons as to why physiological efficiency decreases under saline conditions. Many research workers (Hamid and Ahmad, 1987;Aslam et al, 1989;Zia et al, 1992Zia et al, , 1998 have documented similar conclusions. From the results, it is clear that efficiency of N fertilizer was maximum when N was applied as a mixture of urea and ammonium sulphate at both the rates (600 and/or 800 mg N potG 1 ).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation